The Polybrominated Diphenyl Ether Bromoxib Disrupts Nuclear Import and Export by Affecting Nucleoporins of the Nuclear Pore Complex - Karina S. Krings; Anastasia Ritchie; Laura Schmitt; Judith Hatzfeld; Gudrun Totzke; Thomas Lenz; María José Mendiburo; Björn Stork; Nicole Teusch; Peter Proksch; Kai Stühler; Lisa Müller; et al. (Marine Drugs)
Polybrominated diphenyl ethers (PBDEs) are natural products with potent antimicrobial and antineoplastic activity. We have previously shown that the polybrominated diphenyl ether bromoxib (4,5,6-tribromo-2-(2′,4′-dibromophenoxy) phenol), isolated from the marine sponge Dysidea species, exhibits a strong cytotoxic potential in leukemia and lymphoma cells by targeting mitochondrial metabolism. Here, using a mass spectrometric thermal proteome profiling (TPP) approach, we observed that bromoxib induces a rapid reduction in the levels of 19 nucleoporins (NUPs) that are part of the nuclear pore complex (NPC). This apparently affected the functionality of the NPC, as evidenced by the bromoxib-mediated inhibition of the nuclear translocation and subsequent gene reporter activity of transcription factors such as nuclear factor of activated T cells (NFAT) and nuclear factor κB (NF-κB). In addition, bromoxib inhibited the nuclear export of the mRNA of the human immunodeficiency virus transactivator of transcription (HIV-Tat) and the subsequent import of the HIV-Tat protein into the nucleus as determined by the decrease in Tat-dependent gene reporter luciferase activity. Inhibition of nuclear mRNA-export also affected expression of the short-lived anti-apoptotic Bcl-2 protein Mcl-1, which has been shown to induce apoptosis. Thus, its ability to target both mitochondrial metabolism and the NPC renders bromoxib a promising anticancer agent.